Pengaruh Kepuasan Magang dan Kompetensi Individu terhadap Motivasi Karier Peserta Magang di Bidang Perhotelan - Nurul Hikmah; Hermansyah Hermansyah; Violintikha Harmawan; Melta Sari Ginting (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
The purpose of this study is to examine how individual competence and internship satisfaction affect trainees' career motivation at Harris Resort Barelang Batam. This study employed a quantitative approach with a causal-associative research design. Purposive sampling was used to select 80 respondents from the study population, consisting of trainees from Batches 14 and 15 at Harris Resort Barelang Batam. Data were collected using a five-point Likert scale questionnaire. The data were analyzed using multiple linear regression with SPSS version 27, supported by validity, reliability, classical assumption, t-test, and F-test analyses. The findings indicate that internship satisfaction has a positive and significant effect on career motivation (β = 0.161; p = 0.025). In addition, individual competence has a positive and significant effect on career motivation (β = 0.764; p < 0.001). Simultaneously, internship satisfaction and individual competence have a significant effect on career motivation (F = 19.164; p < 0.001). These findings suggest that trainees' motivation to pursue a career in the hospitality industry can be enhanced through satisfying internship experiences and strong individual competence. Therefore, higher education institutions and industry partners should improve the quality of internship programs while supporting the development of trainees' competencies to strengthen work readiness and career motivation in the hospitality industry.